Specific features of blood and urine cytokine profile in women suffering chronic recurrent cystitis - N. G. Galkina; A. V. Galkin; E. V. Tokareva (Вестник урологии, 2025)
Introduction. Chronic uncomplicated recurrent cystitis denotes the presence of frequent disease exacerbations in the absence of complicating factors. The identification of inflammatory process markers within the bladder wall is of paramount importance, as these markers enable the detection of inflammation in cases of normal urine test results and facilitate the prediction of recurrence risk and the severity of cystitis progression.Objective. To investigate the cytokine profile in blood and urine samples of female patients diagnosed with chronic recurrent cystitis.Materials & methods. The prospective study enrolled 33 female participants with a confirmed diagnosis of chronic (recurrent) uncomplicated cystitis. At the time of blood and urine sample collection, all study participants presented with recurrent chronic pelvic pain and/or pressure, bladder discomfort, and lower urinary tract symptoms. All patients in the study group underwent cystoscopy within bladder wall biopsy. The control group comprised 27 healthy women of reproductive age. The investigation involved the analysis of calprotectin, interleukin-6 (IL-6), tumour necrosis factor, and vascular endothelial growth factor (VEGF) levels in urine and blood samples from both study groups.Results. Statistically significant differences were identified in the levels of blood calprotectin, vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), and urine calprotectin. The concentrations of these cytokines were elevated in the study group compared to the control group. Notably, while Student’s t-test for blood calprotectin approached the significance threshold (p ≈ 0.05), urine calprotectin demonstrated robust diagnostic significance (p = 0.0000). Elevated urinary VEGF levels were observed in the study group patients, suggesting an association with bladder wall hypoxia and inflammation. A direct moderate-strength correlation was established between chronic recurrent cystitis and both urinary calprotectin (R = 0.649, p = 0.0000) and leukocyturia (R = 0.519, p = 0.0000). Pathomorphological examination of the bladder wall in all study group patients revealed an inflammatory process, with 63.6% of cases exhibiting squamous cell metaplasia of the urothelium in the Lieto triangle. The potential key role of increased S100A8/ S100A9 expression on the bladder squamous cell epithelium surface in urinary disorders and chronic processes cannot be ruled out. Importantly, our data indicate that calprotectin can induce abacterial inflammatory processes in the bladder wall without concomitant leukocyte elevation in urine. Consequently, calprotectin exhibits particularly high diagnostic value as a bladder wall inflammation marker, especially in cases of normal urine test results.Conclusion. The study demonstrates significantly elevated levels of urinary calprotectin, vascular endothelial growth factor (VEGF), and interleukin-6 (IL-6) in female patients diagnosed with chronic recurrent cystitis. Notably, the presence of leukocyturia does not influence urinary calprotectin and VEGF concentrations.Calprotectin emerges as a promising biomarker for detecting inflammation within the bladder wall. Its utility extends to both assessing the inflammatory process activity and evaluating therapeutic efficacy.